Histone Deacetylase 3-Mediated Inhibition of microRNA-19a-3p Facilitates the Development of Rheumatoid Arthritis-Associated Interstitial Lung Disease - Yuan, Hui; Jiao, Li; Yu, Nan; Duan, Haifeng; Yu, Yong; Bai, Yanrong (Frontiers in Physiology, 2020)
Histone deacetylase has been implicated in rheumatoid arthritis (RA) progression. We investigated roles of histone deacetylase 3 (HDAC3) involved in RA-associated interstitial lung disease (ILD) fibrosis. Firstly, we measured the expression of HDAC3 and IL17RA in lung tissue samples from normal controls, idiopathic pulmonary fibrosis (IPF) patients, and RA-ILD patients. Next, chromatin immunoprecipitation (ChIP) and dual luciferase reporter assay were employed to detect the interaction between HDAC3 and microRNA-19a-3p (miR-19a-3p) and between miR-19a-3p and IL17RA. Further, immunohistochemistry was used to localize HDAC3 and IL17RA (interleukin 17 receptor A) expression in lung tissues. Additionally, functional assays were conducted followed by expression determination of HDAC3, miR-19a-3p, and IL17RA with RT-qPCR and Western blot analysis. The effect of HDAC3 on RA-ILD in the constructed RA-ILD mouse model was also studied based on arthritis assessment. We found overexpressed HDAC3 and IL17RA as well as silenced miR-19a-3p in RA-ILD mouse model and RA-ILD patients. In the mouse model, HDAC3 down-regulated miR-19a-3p in lung fibroblasts to promote the progression of RA-ILD fibrosis. In lung fibroblasts of RA-ILD mice, IL17RA was a target gene of miR-19a-3p. miR-19a-3p negatively regulated IL17RA, thereby increasing the expression of fibrosis markers, COL1A1, COL3A1, and FN, in lung fibroblasts of mice. Taken together, HDAC3 up-regulated IL17RA expression by targeting miR-19a-3p to facilitate the RA-ILD fibrosis development, which sheds light on a new HDAC3/miR-19a-3p/IL17RA axis functioning in RA-ILD fibrosis.